Losartan reduces liver expression of plasminogen activator inhibitor-1 (PAI-1) in a high fat-induced rat nonalcoholic fatty liver disease model - Rosselli, Maria Soledad (2009)
OBJECTIVE: To evaluate the effect of losartan-an angiotensin II type 1 receptor (AT1R) antagonist- and telmisartan-an AT1R blocker with insulin-sensitizing properties-, on the hepatic expression of plasminogen activator inhibitor-1 (PAI-1) in a rat model of nonalcoholic fatty liver disease (NAFLD). METHODS: Rats were given a high-fat diet (HFD) for 8 weeks and after this period were randomly divided into 3 groups. For 12 weeks along with the same access to HFD, one group (9 rats) received losartan and another group received telmisartan (10 rats), both at 10mg/kg intraperitoneally (ip) every 24h. The third group (8 rats) received saline ip along with the HFD. Finally, a control group (6 rats) was fed with standard chow diet for 20 weeks. RESULTS: Fatty liver was reverted by both losartan and telmisartan. Both drugs had beneficial effects on insulin resistance, reaching statistical significance in telmisartan group. Expression of hepatic mRNA of PAI-1 showed a 42% decrease in losartan-treated rats in comparison with both HFD group and telmisartan-treated rats. To further evaluate this differential effect on PAI-1 expression, we explored the effect of the drugs on liver expression of TNFalpha, PEPCK-C and PPARalpha, and no significant differences were observed. CONCLUSION: These results indicate that AT1R blockers could be eligible drugs for reducing hepatic lipid accumulation in patients with NAFLD. However, only 12 weeks of losartan treatment strongly reduced hepatic PAI-1 gene expression. These differences could provide even more effective options for preventing fatty liver disease and its cardiovascular complications.